alternative approaches to global human needs - Inter-University Consortium for International Social Development (NY., 2004)
Published by: Inter-University Consortium for International School Development in cooperation with the Center for Social Development - George Warren Brown School of Social Work - Washington University in St. Louis; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social service -- Periodicals; Social work education -- Periodicals; Dịch vụ xã hội -- Xuất bản phẩm định kỳ; Giáo dục công tác xã hội